Effect of medical mask on voice in patients with dysphonia - Jing‐Lin Su; Jing Kang; Qin‐Yi Ren; Zhi‐Xian Zhu; Si‐Yi Zhang; Ping‐Jiang Ge (World Journal of Otorhinolaryngology-Head and Neck Surgery)
Abstract Objective Medical masks have been shown to significantly influence speech communication in healthy people. The effect of mask‐wearing on phonatory capability and daily communication exchanges in patients with voice disorders remains unclear. To evaluate the effect of the medical mask on acoustic parameters in patients with a voice disorder, we measured the voice frequency, quality, and intensity. Methods Thirty‐three healthy and 44 voice disorder patients were involved in this study, including 27 patients with vocal‐fold lesions and 17 with primary functional dysphonia. Perceptual evaluation and acoustic parameters, including F0 (fundamental frequency), jitter, shimmer, and maximum vocal intensity, were analyzed without and with medical masks. Results With medical mask‐wearing, the maximum vocal intensity significantly decreased in all patients with voice disorders (p < 0.05), especially in patients with lesions of vocal folds (p < 0.05) and functional dysphonia (p < 0.05). The perceptual evaluation roughness scales also increased in patients with lesions of vocal folds (p < 0.05) and functional dysphonia (p < 0.05) with mask‐wearing. There were no significant effects of mask‐wearing on acoustic parameters for healthy participants. Conclusions The intensity was influenced when wearing medical masks in patients with disordered voices. The voice perceptual roughness scales also significantly increased compared to those without medical masks.